«Dentro quali sguardi ti muovi?»: Strategie fototestuali ne “La Resistenza delle donne” di Benedetta Tobagi (TEST Ticontre. Theory Text Translation, 2026)
This paper examines the phototextual strategies employed by Benedetta Tobagi in La Resistenza delle donne (Einaudi, 2022), a hybrid work in which the dialogic interplay between visual and essayistic narrative codes reshapes the historical discourse on women’s Resistance. The analysis is framed within two theoretical axes: visual culture and phototext theory on one hand, and critical reflection on the essay as a liminal literary form on the other. Through a montage-based structure, the interweaving of oral, memorial, and literary sources, and the author-narrator’s discursive stance, the work constructs a polyphonic and counter-hegemonic memory. The phototext thus emerges as a critical device capable of redefining the relationship between testimony and representation, between the visible and the sayable, within an intermedial perspective that questions the very genealogy of historical narration.